Analisis Persebaran Pasien Rehabilitasi Narkoba di Jawa Tengah pada Tahun 2023-2024 - Bambang Agus Herlambang; Safira Indah Utami (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study aims to analyze the distribution of drug rehabilitation patients in Central Java during 2023 to 2024. The data used is secondary data obtained from various rehabilitation institutions and related health agencies. Geographic distribution mapping was conducted to identify the distribution pattern of patients based on factors such as geographic location, age, gender, and type of drug used. The results showed a significant variation in the distribution of patients, which can be the basis for developing more effective and targeted rehabilitation policies.